Isotropy frequency-domain extension imaging and its application in detection of nanostructures - Bai, Jinxi; Ren, Huan; Shi, Zhendong; Ma, Hua; Liu, Lijia; Ma, Ke; Chai, Liqun; Zhang, Lin (Frontiers in Physics, 2022)
A wide-field high resolution microscopy with sub-diffraction resolution and high contrast image was demonstrated by using the isotropy frequency-domain extension imaging (IFEI), which was successfully applied to submicron-scale structure detection of fused silica wafer for the first time. Employing the frequency-domain extension and the isotropic period matching, the IFEI extended the bandwidth of coherent transfer function of the conventional wide-field microscopy, thereby improving the resolution to break the diffraction limit. In this method, a quantitative high resolution measurement of 200 nm was achieved using fused silica wafer with prefabricated etched structure on the surface. By imaging 81 nm gold nanoparticles, the system resolution calibration was achieved. And corresponding system’s lateral resolution of approximately 179.5 nm was obtained, which was 1.7 times higher than the conventional wide-field microscopy image. Moreover, the reconstructed IFEI images of ultra-precision processed fused silica optics were demonstrated to present the finer structures of sub-micron digs and scratches formed in the optics manufacturing process, which made it possible to study the behavior and mechanism of high damage threshold defects-induced laser damages on fused silica optics.